IMPLEMENTASI EVALUASI SISTEM PEMBELAJARAN DI SEKOLAH - Zainal Abidin; Diana Wangsih (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
The purpose set in this determination is to find out how the implementation of learning evaluation in SMA Darussalam Blokagung 2019/2020 school year. This study uses descriptive qualitative, data collection through interviews, observation, and documentation. Data analysis uses three model interatives, while the data validity technique uses triangulation. The results of this study indicate that the implementation of learning evaluation in SMA Darussalam Blokagung has been implemented quite well, this can be seen from the learning process carried out by the teacher starting from the planning process, implementation, monitoring, management, reporting, and the use of learning evaluation results that have been went well although in the implementation there are still some obstacles. That way the teacher is expected to be better at carrying out each stage of the preformance evaluation of learning in the classroom.